Moisture diffusion measurement and evaluation for porous membranes used in enthalpy exchangers. (February 2019) - Albdoor, Ahmed K.; Ma, Zhenjun; Cooper, Paul
Abstract: Air-to-air membrane enthalpy exchangers using semi-permeable membranes are widely used in building ventilation systems to pre-condition the supply air by exchanging energy with the exhaust air stream. Moisture diffusivity is one of the most important properties of porous membranes. This property has a significant influence on the design and performance of membrane enthalpy exchangers. In this study, moisture diffusion resistances of five porous membranes were measured, and the effects of the membrane pore size on the moisture diffusivity were evaluated under different test conditions. The five porous membranes tested included: i) two PVDF (Polyvinylidene difluoride) membranes with mean pore diameters of 0.22 µm and 0.45 µm respectively, ii) two Nylon membranes with 0.1 µm and 0.45 µm pore sizes respectively, and iii) a PES (Polyethersulfone) membrane with a 0.1 µm pore size. A theoretical model to predict the effectiveness of a crossflow membrane enthalpy exchanger was also developed with respect to the latent heat transfer. The experimental results showed that the PVDF membrane with a mean pore diameter of 0.45 µm outperformed the others in terms of the moisture diffusivity. The results from the theoretical model of the enthalpy exchanger agreed well with those from the experiments reported in the literature. The latent effectiveness was found to be insensitive to the outdoor air conditions.